Evaluation of Common Carp (Cyprinus carpio) Cultivation Techniques at Balai Benih Ikan (BBI) Lingsar, West Nusa Tenggara - Aeni, Nurul; Diamahesa, Wastu Ayu (Journal of Fish Health, 2024)
This research aims to evaluate the cultivation techniques of common carp (Cyprinus carpio) at the Balai Benih Ikan Lingsar Installation, West Nusa Tenggara. The research method involved observation, interviews, and common carp cultivation activities. Data collected included pond preparation, seed selection and stocking, feed management, carp seed growth, evaluation of survival rate (SR), feed conversion ratio (FCR), and water quality measurement. The research results showed significant growth in common carp seeds, with average weight and length increasing from the beginning to the end of the rearing period. The survival rate (SR) reached 97%, while the feed conversion ratio (FCR) reached 0.77, indicating good feed efficiency. Water quality during the common carp cultivation period was within the optimal range, with pH, dissolved oxygen (DO), and temperature values suitable for fish growth. This research demonstrates that the common carp cultivation techniques applied at the Balai Benih Ikan Lingsar Installation are effective in supporting the growth and survival of common carp.